Sentidos associados à tuberculose por idosos e profissionais de saúde - Batista, Tatiana Pimentel de Andrade (2017)
The human sickness caused by Tuberculosis is secular. The disease has killed and decimated populations on all continents leaving deep marks because of their social impact. Hence the importance of exploring the social representations about tuberculosis in the eyes of the elderly and professionals who experience tuberculosis, it is of singular importance to know what they think about the disease. In this sense, this study aims to identify the social representations about tuberculosis constructed by the elderly and to analyze the social representations about tuberculosis by health professionals. It is an exploratory, with a qualitative approach, based on the Theory of Social Representations. Held at the Family Health Units of the Municipality of João Pessoa / Paraíba / Brazil, with 258 elderly and 248 health professionals. A semistructured interview was adopted, contemplating in the first part the Free Association of Words, with the term inductor: "Tuberculosis" and in the second part, socio-demographic data. Empirical data were organized into a database, then processed using the software IRaMuTeQ version 0.7 alpha 2. Two articles emerged. The first article, with 258 elderly people, in which the majority were female, 70.5% (182), had an age group of 73.3% (189) were aged 60 to 79 years, 44.7% (115) Were married, 40.3% (104) had over 8 years of schooling. Three classes emerged: Class 3: psychosocial descriptions of symptomatology, with 86 (36.23%) text segments, brings the representations constructed mainly by the group of elderly people with undefined schooling; And Class 1: descriptions of treatment and care for tuberculosis, was formed by 110 (47.62%) retained text segments, had greater contribution of the group of elderly people over 80 years; Class 2: negative dimensions of tuberculosis, built mainly by the group of elderly people with education under 1 year of basic education, with 35 text segments, equivalent to 15.15% of the retained follow-up. The second article shows that the majority of the subjects were female, 85.9% (213), aged 31 to 59 years, making up 70.6% (175) of the subjects, nurses 22.6% (56), with Service with 0 to 10 years 69.8% (173). Three classes emerged: Class 3, Descriptions of the symptomatology, formed by 25,13% (50) retained follow-ups, had greater contribution of professionals trained in dentistry, in their evocations the professionals correlate the words Tuberculosis, formed by 20.6% 41) Retained Text Followers, the professionals who contributed most to the classes were those in the training groups in physical therapy, physical education, social work and nutrition. According to class 2, descriptions on the treatment of tuberculosis, constituted by 54.27% (108) followups, formed mainly by the group of nurses. Considering the meanings attributed to tuberculosis, the psychosocial aspects, expressed refer to the psychological factors suffered by the sick population. It is known that the stigmas influence in a negative way from the diagnosis as well as the adherence to the treatment, delaying or preventing cure of the disease. The health professional plays a very important role in the elaboration of the actions and strategies involved, as well as in the search for a dignified treatment, to contribute to the transformation of stigmatized discourse. Finally, it is suggested that care practices be redirected to health education, considering the singularities of professionals and different social realities.